UMPSA Advances Global Education Goals at EURIE 2025 - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
ISTANBUL, 7 April 2025 – Universiti Malaysia Pahang Al Sultan Abdullah (UMPSA) strengthened its commitment to inclusive global education through its participation at the 10th Eurasia Higher Education Summit (EURIE 2025), held at the Istanbul Lütfi Kırdar International Convention and Exhibition Centre.